2022
DOI: 10.1038/s41598-022-19203-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain-correlates of processing local dependencies within a statistical learning paradigm

Abstract: Statistical learning refers to the implicit mechanism of extracting regularities in our environment. Numerous studies have investigated the neural basis of statistical learning. However, how the brain responds to violations of auditory regularities based on prior (implicit) learning requires further investigation. Here, we used functional magnetic resonance imaging (fMRI) to investigate the neural correlates of processing events that are irregular based on learned local dependencies. A stream of consecutive so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…However, hierarchical structure processing could co-exist with simpler, shallower, and perhaps evolutionarily older mechanism for local, word-by-word predictions. Indeed, the co-existence of two distinct mechanisms was already identified in the case of the processing of sequences of nonlinguistic items (23)(24)(25)(26)(27)(28)(29). Specifically, using the Local-Global Paradigm, a variant of the oddball auditory paradigm, Bekinschtein et al (23) showed that transition-based (local) processing can be distinguished from that of chunking (global) and from possibly higher levels, each eliciting distinct violation signals in different brain areas and timings (30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…However, hierarchical structure processing could co-exist with simpler, shallower, and perhaps evolutionarily older mechanism for local, word-by-word predictions. Indeed, the co-existence of two distinct mechanisms was already identified in the case of the processing of sequences of nonlinguistic items (23)(24)(25)(26)(27)(28)(29). Specifically, using the Local-Global Paradigm, a variant of the oddball auditory paradigm, Bekinschtein et al (23) showed that transition-based (local) processing can be distinguished from that of chunking (global) and from possibly higher levels, each eliciting distinct violation signals in different brain areas and timings (30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%